Family Empowerment through Psychosocial Stimulation Assistance and Child Feeding in Increasing Nutrition Intake and Body Weight of Children 2-3 Years Old to Prevent Stunting - Sukmawati; Fatmawati Suaib (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The prevalence of stunting in Indonesia still high based on Basic Health Research 2018 withprevalence 30.8%. The percentage of children under five with stunting in South Sulawesi more increasing,from the results ofBasic Health Research in 2007, 2010, and 2013, respectively 29.2%, 39.8%, and 40.9%.In 2018, the position of South Sulawesi on the fourth highest prevalence of stunting from all provinces inIndonesia. The extent andheight number of children under five with stunting in South Sulawesi have a verybig impact on the quality of human resources in the future(1)(2).Objective: The aims of this study to analyze the effect of family empowerment through psychosocialstimulation assistance and child feeding on nutritional intake and body weight of children aged 2-3 years toprevent stunting.Methods: The research design and type wasquasi-experimentalwith the Pre-Post Test Control Group Design.The sample of this research is 30 children under five aged 2-3 yearsat PaccerakangHealth Center, MakassarCity. The analysis data using Paired T-Test.Results: There was an increaseintake of carbohydrates, protein, fat, calcium, zinc, and vitamin A, whichwas higher in the treatment group than in the control group. There was an increase in body weight in thetreatment group which was higher at 0.35 kg while in the control group it was only 0.08 kg.Conclusion: Family empowerment through psychosocial stimulation assistance and child feeding has asignificant effect on increasing nutrient intake (carbohydrates, protein, fat, calcium, zinc, and vitamin A) andbody weight of children aged 2-3 years. It is hoped that puskesmas officers and posyandu cadres will providemore assistance to mothers of toddlers on psychosocial stimulation and child feeding.